2019
DOI: 10.1183/13993003.02077-2018
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for programmatic management of latent tuberculosis infection in the European Union/European Economic Area

Abstract: @ERSpublications Management of latent tuberculosis infection is crucial to end TB in low-incidence settings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…In settings with a low annual TB incidence (<10 cases per 100,000 population) current WHO guidelines recommend preventive therapy (PT)-which can decrease TB occurrence by 60-90% [5]-for people living with HIV, for adult contacts of TB patients, and for other clinical risk groups (e.g., homeless persons) [6]. Furthermore, depending on the migratory flows, a country may implement screening programs and LTBI PT for those who had recently arrived (e.g., asylum seekers/refugees) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In settings with a low annual TB incidence (<10 cases per 100,000 population) current WHO guidelines recommend preventive therapy (PT)-which can decrease TB occurrence by 60-90% [5]-for people living with HIV, for adult contacts of TB patients, and for other clinical risk groups (e.g., homeless persons) [6]. Furthermore, depending on the migratory flows, a country may implement screening programs and LTBI PT for those who had recently arrived (e.g., asylum seekers/refugees) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Generally infection control measures to protect HCW, including personal protective equipment and proper ventilation, undertaken in high or medium incidence countries, are not adequate, and are not a priority. Moreover, HCW were not listed as a separate risk group of infection in the recently published guidance for programmatic management of LTBI in the European Union/European Economic Area [14]. In Poland and in many Tb endemic settings, screening for LTBI among HCWs is very limited in practice and preventive treatment is almost never considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that one quarter of the world's population are latently infected with TB (LTBI) (Houben and Dodd, 2016), and a recent meta-analysis of prevalence surveys confirmed that 20-25% globally have LTBI (Cohen et al, 2019). This is a challenge for both high and low endemic countries, but it is evident that to reach the World Health Organization (WHO) End TB goal, the reservoir of LTBI has to be eliminated or reduced significantly (WHO, 2015;Petersen et al, 2019;Rosales-Klintz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%